International Versus Domestic Auditing of Bank Solvency - Feltenstein, Andrew (IMF Working Papers; Working Paper ;, 2003)
This paper examines alternative ways to prevent losses from bank insolvencies. It is widely viewed that transparency in reporting bank balance sheets is a key element in reducing such losses. It is, however, unclear just how such transparency would be achieved. Current approaches to avoiding insolvencies generally involve international enforcement mechanisms. Among these are the sovereign debt restructuring mechanism (SDRM), and, more generally, an international bankruptcy court. We develop a model that compares two alternative institutions for bank auditing. Neither of these institutions would require as much enforcement capability as an international bankruptcy court, hence they would be easier to introduce. The first of these is a system of central bank auditing of national banks. The second type of auditing is carried out by an international agency that collects risk information on banks in all countries and then provides it to depositors. Using a game-theoretic approach, we compare the informativeness of the disclosure rule in the symmetric Perfect Bayesian equilibrium in each of the two different auditing institutions. We show that the international auditor generally performs at least as well, and sometimes better than, auditing by either central banks, which, in turn, perform better than voluntary disclosure by the banks themselves. The results do not assume any informational advantages of the international auditor, nor is the international auditor somehow less "corrupt" than the central banks. Rather, the international auditor's credibility comes from the simple fact that its incentives are not distorted by a sovereignty bias that plagues the central banks.